OBSTETRIC COMPLICATIONS IN ENDOMETRIAL-ASSOCIATED INFERTILITY - Светлана Ивановна Елгина; Александра Александровна Митроченко; Валерия Дмитриевна Фетюхина; Елена Владимировна Рудаева; Наталья Степановна Черных; Кира Борисовна Мозес (Мать и дитя в Кузбассе)
Endometriosis is a chronic pathological process in which the presence of tissue similar to the endometrium outside the uterine cavity is determined, which has a high social significance and is associated with various clinical manifestations, including infertility.